Investigating madrasa students’ self-efficacy in English language learning: Survey research in a public madrasa in Bandung - Lestari, Zubaedah Wiji (Englisia Journal, 2025)
The researcher observed that most students at State Madrasa 2 Bandung lack confidence in learning English. This lack of confidence arises from anxiety about making mistakes when speaking English and concerns about failing to meet learning objectives. To address this issue, the present study evaluates the self-efficacy levels of a single class of twelfth graders at a State Madrasa in Bandung regarding English learning. The study adopted a quantitative approach, using descriptive surveys and a series of questionnaires as research instruments. The survey findings revealed that most students exhibited a moderate level of self-efficacy in learning English. According to the questionnaire responses, students’ self-efficacy levels varied from high to low across different topics. Based on these findings, students with high self-efficacy are encouraged to sustain it, while those with moderate or low self-efficacy require teacher support and engagement to improve. Therefore, it is recommended that teachers adopt appropriate strategies and approaches, along with providing motivation, to enhance students’ self-efficacy.